2009
DOI: 10.1089/ten.tec.2008.0286
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Fibrinolysis to Engineer Skeletal Muscle from the C2C12 Cell Line

Abstract: Muscles engineered from transformed cells would be a powerful model for the study of muscle physiology by allowing long-term in vitro studies of muscle adaptation. However, previously described methods either take >5 weeks to produce a tissue or use collagen as a scaffold, which decreases the specific force of the muscle, making it hard to measure the function of the constructs. The aim of this study was to rapidly engineer muscle using the C2C12 cell line in fibrin, which has a stiffness similar to muscle tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 38 publications
3
65
0
Order By: Relevance
“…GM was replenished daily for 3 days, at which point the cells were confluent and the media was switched to differentiation media (DM) consisting of high glucose DMEM containing 2% Horse serum (Sigma–Aldrich), 1% Penicillin‐streptomycin and 0.5 mg/ml 6‐aminocaproic acid. Following 48 hr in DM, media was switched to maintenance media (MM) in accordance with previous reports (Khodabukus & Baar, 2009) consisting of high glucose DMEM, 7% FBS, 1% penicillin‐ streptomycin, and 0.5 mg/ml 6‐aminocaproic acid. MM was changed daily for the duration of the experiment (14 days) and was supplemented with 1, 5, or 20 mM of L‐leucine (Sigma–Aldrich) and/or rapamycin (100 nM; Millipore, Hertfordshire, UK) from day 9 onward for functional, morphological, and mRNA analyses.…”
Section: Methodsmentioning
confidence: 99%
“…GM was replenished daily for 3 days, at which point the cells were confluent and the media was switched to differentiation media (DM) consisting of high glucose DMEM containing 2% Horse serum (Sigma–Aldrich), 1% Penicillin‐streptomycin and 0.5 mg/ml 6‐aminocaproic acid. Following 48 hr in DM, media was switched to maintenance media (MM) in accordance with previous reports (Khodabukus & Baar, 2009) consisting of high glucose DMEM, 7% FBS, 1% penicillin‐ streptomycin, and 0.5 mg/ml 6‐aminocaproic acid. MM was changed daily for the duration of the experiment (14 days) and was supplemented with 1, 5, or 20 mM of L‐leucine (Sigma–Aldrich) and/or rapamycin (100 nM; Millipore, Hertfordshire, UK) from day 9 onward for functional, morphological, and mRNA analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the current methods of generating muscle constructs result in myooids which exhibit significant deficits in force production compared to that of native muscle (Dennis et al, 2001). The absence of fibroblasts in constructs generated from C 2 C 12 cells also resulted in a force deficit manifesting in a 35% reduction in peak twitch force after tetanic stimulation (Khodabukus & Baar, 2009). The authors noted that addition of 3T3 fibroblasts to C 2 C 12 myotubes (ratio 1:5) prior to seeding attenuated this force deficit but lead to a 50% decrease in specific force.…”
Section: Future Applications 61 Three-dimensional Skeletal Muscle Timentioning
confidence: 99%
“…Consistent with this, Hinds et al, (2011) found that the use of a hydrogel matrix consisting of Matrigel and fibrin enhanced myotube formation and density within the construct which was positively correlated with force production. Whilst no single extracellular matrix has been identified conclusively as superior, the use of fibrin gels with aprotinin, a plasminogen inhibitor and the naturally occurring cross-linking agent, genipin, have been shown to enhance force production and time-to-failure of constructs by way of controlled degradation of this matrix (Khodabukus & Baar, 2009). Moreover, fibrin gels provide a more flexible scaffold medium into which cells migrate and proliferate both on top of and within the fibrin gel to increased specific force production (Dennis et al, 2001;Huang et al, 2005).…”
Section: Growth Of Bioengineered Tissue Constructsmentioning
confidence: 99%
See 2 more Smart Citations